Strategi Kepolisian Dalam Mengurangi Pelanggaran Lalu Lintas di Sungguminasa Kabupaten Gowa (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine the preventive and repressive strategies of the police in reducing traffic violations in Gowa Regency. This study used qualitative research by explaining and describing events that actually occured in the field during the study. Data analysis techniques used data reduction, data presentation, and conclusions. The results of this study showed that the strategy carried out by the Gowa Police Station consisted of two types were; a) Preventive strategy, namely Socialization, Giving Brochures and Sticker. b) Repressive strategy that was to carry out zebra operations by acting on offenders in the form of speeding tickets and confiscation. As well as inhibiting factors were knowledge and level of public awareness were still lacking, and bribing. While supporting factors were the collaboration between the police and the school and community, and speeding tickets